Partisipasi Komite Sekolah dalam Manajemen Berbasis Sekolah di Lembaga Pendidikan Islam - Jufri; Abdul Rahim; La Ode Sahrin Djalia; La Ode Fajrul Islam Sabti (Research Institute and Community Engagement of UIN MADURA, 2026)
This study examines school committee participation in improving the quality of Islamic educational institutions through strengthening School-Based Management (SBM). The study was conducted at MA Al-Qoyyuum Hendea, Hendea Village, Sampolawa Subdistrict, South Buton Regency, a madrasah established in 2020 through community self-help initiatives. Using a qualitative case study design, data were collected through semi-structured interviews with the madrasah principal, teachers, committee officers, parents, community leaders, and high-achieving students; limited observations of committee meetings and coaching activities; and document analysis (program plans, meeting minutes, evidence of community contributions, and records of student achievements). Data were analyzed thematically through coding, categorization, and theme development, while trustworthiness was ensured through source method triangulation and member checking. The findings indicate that committee participation is substantive and multidimensional. The committee played a crucial role in mobilizing resources and legitimacy during the madrasah’s establishment, contributed to setting program priorities, and supported quality improvement initiatives especially coaching for science and sports achievements which strengthened public trust. In addition, the committee functioned as a channel for parents’ aspirations and a social mediator to maintain community cohesion. These findings align with social capital and participatory governance perspectives that emphasize trust, shared ownership, and deliberative decision-making. However, the sustainability of participation remains constrained by variations in parents’ capacity, reliance on personal relationships, and insufficiently standardized program–budget documentation. In conclusion, institutionalizing clear procedures, consistent reporting, and indicator based evaluation is necessary to ensure that committee participation yields long-term impacts on madrasah quality.